Resistência de híbridos de milho à podridão de macrophomina e à antracnose do colmo em dois ambientes - Bernardes, Fernanda Pinheiro (2023)
The incidence and severity of corn stalk rot increases in each harvest, especially in maize cultivation in off-season, when climatic conditions such as high temperature and dry occur, favoring pathogens. The fungi Colletotrichum graminicola (stem anthracnose) and Macrophomina phaseolina (charcoal rot) are among the main pathogens that cause stem rot in maize. The sowing of resistant hybrids is considered the main strategy for controlling these diseases, however, there are few reports in the literature regarding the level of resistance of commercial corn hybrids to these pathogens. Thus, the objective of this work was to characterize commercial corn hybrids in terms of resistance to these fungi through artificial inoculation in the field. This dissertation is divided into two chapters, the first chapter is the theoretical framework that addresses the general aspects of the corn crop, the fungi C. graminicola and M. phaseolina and the genetic resistance of plants to diseases. The second chapter aimed to characterize corn hybrids in terms of resistance to both pathogens. Two experiments were carried out in the off-season of 2021/22 in different areas and times, at Fazenda Invernadinha, in Paraíso do Tocantins – TO. In the first experiment there was greater water availability compared to the second, a factor that influenced the severity of the diseases, so that in environment 1 there was a greater severity of anthracnose and in environment 2 a greater severity of macrophomina rot. Among the thirty commercial hybrids evaluated, for stem anthracnose, the resistant materials were B2801 VYHR, P3707 VYH and 20A44 VIP3, and for macrophomina rot, the hybrids K9606 VIP3, NS88 VIP3, CRV2654 PRO2 and P3707 VYH. The hybrid P3707 VYH showed resistance to both diseases.